2022
DOI: 10.2196/33609
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation Into the Use of mHealth in Musculoskeletal Physiotherapy: Scoping Review

Abstract: Background Musculoskeletal physiotherapy provides conservative management for a range of conditions. Currently, there is a lack of engagement with exercise programs because of the lack of supervision and low self-efficacy. The use of mobile health (mHealth) interventions could be a possible solution to this problem, helping promote self-management at home. However, there is little evidence for musculoskeletal physiotherapy on the most effective forms of mHealth. Ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 77 publications
0
19
0
Order By: Relevance
“…Different studies [ 42 , 43 ] suggest that patients prefer individualized, supervised exercise programs with a therapist's opinion. In addition to web-based software, the development of mobile-based telerehabilitation applications can provide patients with personalized and supervised exercise programs and input from therapists [ 44 ]. There is evidence that using mobile apps with therapist input, particularly the ability to set and monitor the quality of exercise completion [ 33 ], leads to higher adherence rates and thus improves musculoskeletal functions than traditional paper handouts.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies [ 42 , 43 ] suggest that patients prefer individualized, supervised exercise programs with a therapist's opinion. In addition to web-based software, the development of mobile-based telerehabilitation applications can provide patients with personalized and supervised exercise programs and input from therapists [ 44 ]. There is evidence that using mobile apps with therapist input, particularly the ability to set and monitor the quality of exercise completion [ 33 ], leads to higher adherence rates and thus improves musculoskeletal functions than traditional paper handouts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found the use of digital interventions in OA care and musculoskeletal physiotherapy to be potentially as effective as standard treatment. 25 40 If deemed to be non-inferior, further integration of digital exercise programmes in the treatment of patients with OA could fulfil the requirement of a personalised treatment approach, creating an option for greater empowerment of the patient. 41 The use of digital solutions may contribute to a sustainable healthcare system in the future.…”
Section: Discussionmentioning
confidence: 99%
“…19 20 Digital health solutions involving web applications, online platforms, telephone and video consultations have shown positive results in the management of OA. [21][22][23][24][25][26] Mobile health (mHealth) is a subset of digital health, involving the use mobile technologies and devices in healthcare, including mobile health applications. 27 The development of mobile health applications is progressing rapidly, with a potential to reach a large part of the OA patient population.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 2 more Smart Citations